Umbrella - Yashima, Tarō, 1908- (New York : Puffin Books, 1977)
Momo eagerly waits for a rainy day so she can use the red boots and umbrella she received on her third birthday.
Caldecott Medal/Honor
Elem. School Library Collection
Wilson's Children
Booklist, April 2008
Bulletin (Center for Children's books), May 1995
Elem. School Library Collection, June 2000
Keywords: Rain and rainfall -- Fiction; Umbrellas -- Fiction; Rain -- Fiction; Umbrellas and parasols -- Fiction